Gawe Rapah sebagai Model Resolusi Konflik Berbasis Kearifan Lokal di Pulau Seribu Masjid, Lombok - Kamar, Mohammad Zaenul; Casmini, Casmini; Sa'adah, Nurus (Jurnal Sosiologi Agama Indonesia (JSAI), 2024)
This study aims to analyze the role of the “gawe rapah” tradition in addressing three forms of violence—direct, structural, and cultural—and to explore its contributions to peacemaking, peacekeeping, and peacebuilding within the multicultural context of Mareje Timur Village, Lombok Island. Employing a qualitative descriptive approach, the research utilizes direct observation, in-depth interviews, and document analysis. Data were analyzed using Galtung's conflict resolution theory. The findings reveal that the “gawe rapah” tradition effectively mitigates direct violence through dialogue, addresses structural inequalities by fostering social inclusion, and reduces cultural violence through tolerance education. Additionally, the tradition contributes to maintaining social stability (peacekeeping) and fostering long-term harmony (peacebuilding), including integration into formal education and the utilization of digital technology. This study underscores the relevance of the “gawe rapah” tradition as a conflict resolution mechanism rooted in local wisdom and highlights its potential to serve as an inclusive and sustainable model for conflict resolution in other multicultural contexts. Abstrak Penelitian ini bertujuan untuk menganalisis peran tradisi “gawe rapah” dalam mengatasi tiga bentuk kekerasan—langsung, struktural, dan budaya—serta mengeksplorasi kontribusinya pada peacemaking, peacekeeping, dan peacebuilding dalam konteks masyarakat multikultural di Desa Mareje Timur, Pulau Lombok. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan observasi langsung, wawancara mendalam, dan analisis dokumen. Data dianalisis menggunakan teori resolusi konflik Johan Galtung. Hasil penelitian menunjukkan bahwa tradisi “gawe rapah” efektif dalam meredakan kekerasan langsung melalui dialog, mengatasi ketimpangan struktural dengan menciptakan inklusi sosial, dan mengurangi kekerasan budaya melalui pendidikan toleransi. Tradisi ini juga berkontribusi pada menjaga stabilitas sosial (peacekeeping) dan membangun harmoni jangka panjang (peacebuilding), termasuk melalui integrasi dalam pendidikan formal dan penggunaan teknologi digital. Kajian ini menegaskan bahwa tradisi “gawe rapah” tetap relevan sebagai mekanisme resolusi konflik berbasis kearifan lokal dan memiliki potensi untuk menjadi model penyelesaian konflik yang inklusif dan berkelanjutan bagi masyarakat multikultural lainnya.